Examination behavior: Gender differences in preferences? - Lena Nekby; Peter Skogman Thoursie; Lars Vahtrik (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2013)
A unique examination strategy in first year microeconomics courses is used to test for gender differences in preferences in examination behavior. Students have the possibility of attaining a seminar bonus on the final exam for near-perfect seminar attendance and are given two voluntary initial quizzes during the semester. At the final exam, the scores received on initial quizzes can either be accepted as is, or students can attempt to improve their marks by answering similar quiz questions on the exam. Results suggest that female students are more likely to take initial quizzes and receive a seminar bonus but are less likely to re-take quiz-questions on the final exam. These results suggest higher risk aversion among female students relative to male students, behavioral differences with tangible implications in terms of final grades on the course.
Keywords: J16; A12; A14; 330; gender; preferences; risk aversion; overconfidence; Bildungsverhalten; Risikoaversion; Studierende; Geschlecht; Schweden